Synthesis and DFT Analysis of Thermoplastic Starch Bioplastics: A Sustainable Alternative for Green Packaging - Mishra, Divyanshi; Saxena, Indu; Gupta, Aditya; Yadav, Preeti (Asian Journal of Chemistry, 2025)
The growing environmental concerns about synthetic polymers have increased the need for biodegradable alternatives made from renewable resources. Starch, a naturally abundant and low-cost polysaccharide, appears to be a potential contender for long-term polymer applications. This work explores the structural and thermo-physical properties of thermoplastic starch (TPS) for use in the sustainable packaging. At 323.15 K, concentration-dependent behaviour was observed, with density increasing from 1026.5 to 1028.4 kg m–3 and viscosity increasing from 1.9855 × 10–3 to 2.1887 × 10–3 Ns m–2 as polymer concentration increased. Acoustic impedance increased proportionally (1606.47 to 1634.13 kg m–2 s–1), but adiabatic compressibility fell from 3.9775 × 10–10 to 3.8511 × 1010 kg–1 ms2, suggesting higher intermolecular interactions. DFT simulations showed that hydration improves the electrical stability of TPS by raising the HOMO-LUMO gap to 15.0763 eV, compared to 14.6969 eV for native starch. Thermodynamic study found that TPS had increased vibrational energy (281.045 kcal/mol) and entropy (187.904 cal/mol-K), confirming structural changes. Global reactivity descriptors indicated an improved chemical hardness (7.5382 eV) and decreased electrophilicity (0.0239 eV), confirmed improved material stability. Molecular docking revealed hydrogen bonding as the fundamental interaction mechanism (binding energy: -1.47 kcal/mol). These findings provide quantitative insights into TPS’s adjustable features, emphasizing its promise as a sustainable alternative to traditional polymers.